ChemInform Abstract: High Temperature Crystallographic and Thermodynamic Investigations on Synthetic Calzirtite (Ca2Zr5Ti2O16). Issue 35 (11th August 2016) - Jafar, Mohsin; Phapale, Suhas B.; Nagabhusan Achary, S.; Mishra, Ratikanta; Tyagi, Avesh K.
Abstract: The title material is characterized by variable temperature powder XRD and high temperature solution calorimetric measurements.